Gum Arabic Microencapsulation of Zingiberaceae family Rhizome Extracts (C. longa, C. xanthorriza and Z. officinale) Using Spray Drying Processing and Its Characterization - Ramli, Nurul Natasah Haziqah; Mohd Kassim, Angzzas Sari (Progress in Engineering Application and Technology, 2023)
Most research have been found that Zingiberaceae family. contain bioactive compound that contains high antioxidant, antimicrobial and anti-inflammatory properties. Among those Curcuma sp. and Zingiberaceae family, three type of the species have yield high properties of antioxidant, antimicrobial and anti-inflammatory. The extraction of bioactive compounds from traditional medicine and their incorporation into contemporary treatment have advanced. Spray drying is the procedure used to encapsulate the extracted bioactive component. This study has been conducted to microencapsulated Zingiberaceae family Rhizome Extracts (C. longa, C. xanthorriza and Z. officinale) using spray drying processing and to analysed the physiochemical properties of the microencapsulated Zingiberaceae family. extracts based on the physical, structural, and chemical properties. We also evaluate the efficiency of the extracts in terms of its anti-inflammatory of the plant extracts. Total phenolic content is calculated using the Folin-ciocalteu technique, whereas BSA assays is used to measure anti-inflammatory of the extracts. Spray drying was used to create the granules of temulawak, ginger, and turmeric that will be encapsulate by using Gum Arabic. The input temperature was 180°C, the blow rate was 40 m3/h, and the pump speed was 5 rpm. In conclusion, temulawak, ginger and turmeric yield high bioactive compound in them that contain high anti-inflammatory. After being microencapsulate using spray drying, turmeric would be the best plant that display the highest bioactive compound presented after being encapsulate with a carrier. This finding of this study will affect the diversification of medical plants in health, cosmeceutical and food sector.